2004
DOI: 10.1001/archotol.130.8.923
|View full text |Cite
|
Sign up to set email alerts
|

Confocal Reflectance Imaging of Head and Neck Surgical Specimens

Abstract: Background: Confocal reflectance microscopy (CRM) is an optical method of imaging tissue noninvasively without the need for fixation, sectioning, and staining as in standard histopathologic analysis. Image contrast is determined by natural differences in refractive indices of organelles and other subcellular structures within the tissues. Gray-scale images are displayed in real time on a video monitor and represent horizontal (en face) optical sections through the tissue. We hypothesized that CRM is capable of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…34 A study published by White et al in 1999 comparing in vivo confocal reflectance imaging of normal oral tissue with histology established the foundation for in vivo confocal imaging for disease detection in oral mucosa. 34 The confocal images presented by White et al correlated well, both qualitatively and quantitatively, with histology. Epithelial cell nuclei and cell borders, circulating blood cells, and extracellular matrix were imaged with confocal microscopy.…”
Section: Discussionmentioning
confidence: 72%
“…34 A study published by White et al in 1999 comparing in vivo confocal reflectance imaging of normal oral tissue with histology established the foundation for in vivo confocal imaging for disease detection in oral mucosa. 34 The confocal images presented by White et al correlated well, both qualitatively and quantitatively, with histology. Epithelial cell nuclei and cell borders, circulating blood cells, and extracellular matrix were imaged with confocal microscopy.…”
Section: Discussionmentioning
confidence: 72%
“…[8][9][10][11][12][13][14][15][16] Compared with the wider use of the in vivo confocal microscopy, ex vivo tissue assessment has been performed mainly in skin oncology to examine excision margins in Mohs surgery; 17 only few studies have focused on different tissues. [18][19][20][21][22][23][24][25][26] In surgical oncology, the possibility to obtain a reliable histopathologic diagnosis in a short time represents a relevant clinical advantage for patient management. Nowadays histopathologic diagnosis is routinely rendered through intraoperative frozen tissue examination when a rapid diagnosis is required.…”
mentioning
confidence: 99%
“…CRM is based on the mechanism of backscattering of light. This is primarily determined by natural differences in the refractive indices of organelles and other subcellular structures within the tissues (White et al 2004). Basically, the CRM set consists of a light source, a condenser, an objective lens, and a detector.…”
Section: Confocal Reflectance Microscopymentioning
confidence: 99%
“…The researchers suggested the potential of CRM in the clinical evaluation of oral lesions, early diagnosis of oral PMDs and oral cancer, real-time identification of tumor margins, and monitoring of the response to therapeutic treatment (Clark et al 2003; Anuthama et al 2010). However, in an pilot study, when the researchers examined the microscopic anatomy of freshly excised head and neck surgical specimens using CRM, and compared the findings with those generated by conventional histologic analysis, they found that there were fewer microscopic details visible in the CRM images than in paraffin-embedded histologic sections (White et al 2004). …”
Section: Confocal Reflectance Microscopymentioning
confidence: 99%